The rights to freedom of expression and privacy in the Council of Europe’s instruments – a dynamic and precarious balancing act - Urška Umek (Chrześcijaństwo-Świat-Polityka)
The article shows how the legal instruments of the Council of Europe and the case law of the European Court of Human Rights balance the right to freedom of expression and the right to privacy.